Steamboat MONARCH, probably the lower Yukon River, probably between 1898 and 1927 - University of Washington Libraries. Special Collections Division. (1898)
Built in 1898 and abandoned in 1927. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number